2018
DOI: 10.1038/s41598-018-27818-y
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic salmon skin barrier functions gradually enhance after seawater transfer

Abstract: Atlantic salmon farming operates with high production intensities where skin integrity is recognized as a central factor and indicator for animal health and welfare. In the described trial, the skin development and its immune status in healthy Atlantic salmon reared in two different systems, a traditional open net-pen system and a semi-closed containment system, were investigated. Freshwater smolts were compared to post-smolts after 1 and 4 months in seawater. Growth performance, when adjusted for temperature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 38 publications
2
35
0
1
Order By: Relevance
“…Elevated skin mucous cell numbers are generally reflective of healthy fish whereas depleted mucosal cells may indicate a recent mucosal discharge due to stress or disease (63, 64). Mucosal cell numbers however, can also be influenced by the sampling location on the fish body, sex, diet, and age or development stage, thus care must be taken when interpreting results (31, 65, 66). In our study, skin and gill mucosal cell numbers were elevated in both RAS systems compared to the FT suggesting that RAS fish may have been more healthy or less stressed.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated skin mucous cell numbers are generally reflective of healthy fish whereas depleted mucosal cells may indicate a recent mucosal discharge due to stress or disease (63, 64). Mucosal cell numbers however, can also be influenced by the sampling location on the fish body, sex, diet, and age or development stage, thus care must be taken when interpreting results (31, 65, 66). In our study, skin and gill mucosal cell numbers were elevated in both RAS systems compared to the FT suggesting that RAS fish may have been more healthy or less stressed.…”
Section: Discussionmentioning
confidence: 99%
“…The number of cells in the intermediate epidermal compartment varies with age, species and other factors such as temperature (Elliott 2011; Karlsen et al . 2018). These cells supply and replace dead cells of the superficial layer.…”
Section: The Anatomy and Functions Of Fish Skinmentioning
confidence: 99%
“…The biological interpretation of RNA-seq (RNA sequencing) (whole transcriptome sequencing) remains challenging and depends on availability of well-annotated genomes, which remain uncommon in nonmodel and noncommercial fish species [166]. Gene expression and transcriptomics have been successfully used to characterize the mucosal responses following bacterial infections in fish and after salmon smoltification [173][174][175][176]. A recent genome study of Atlantic salmon found seven putative mucin genes with tissue-specific transcription patterns, and it revealed that mucin transcription is regulated differently by different aquaculture stressors, providing new insights into mucosal health [177].…”
Section: Use Of "Omics" In Fish Mucus Researchmentioning
confidence: 99%